Marketing Strategies in Increasing the Attractiveness of Travel Service Users PT Cahaya Bintang Holiday - Wita, Risma; Mubarak, Husni (Journal of Economic, Management, Accounting and Technology (JEMATech), 2025)
This research discusses the marketing strategy of PT Cahaya Bintang Holiday in improving promotion and service of tour and travel agency services through various approaches. First, the power of social media such as TikTok and Facebook is used by companies to promote products and services, so that they can attract the attention of many audiences to buy and use these services. Second, good service is a key factor in a company's success, especially in the service sector. The excellent service provided by PT Cahaya Bintang Holiday focuses on customer comfort and service quality which continues to be improved, especially after the COVID-19 pandemic. Third, outreach to the surrounding community through a family approach is carried out to get closer to the community and tourists, and attract their interest in the travel programs offered. The research uses a qualitative approach by conducting interviews with informants, especially employees and staff who know marketing strategies and attractiveness. This research also identifies supporting and inhibiting factors in the company's marketing strategy. The research results show that the S-O strategy implemented includes increasing sales promotions and product and service quality innovation. W-O's strategy includes increasing promotions through social media, developing market segments, and increasing human resources. The S-T strategy focuses on improving service quality, while the W-T strategy aims to improve promotion and human resources and maintain good relations with existing transportation.